Nonoperative Management of the Adult Spinal Deformity Patient: A Biopsychosocial Intervention Versus Care-as-usual - A Comparative Treatment-Based Cohort Study With One-Year Follow-Up - Evelien H. W. Hoevenaars; Michiel Beekhuizen; Ahmet Alanay; Yann Philippe Charles; Frank Kleinstueck; Ibrahim Obeid; John O’Dowd; Ferran Pellisé; Javier Pizones; Maarten Spruit; Marinus de Kleuver; Miranda L. van Hooff (Global Spine Journal, 2026)
Study design Comparative Cohort Study. Objectives The aim of this study was to compare a biopsychosocial intervention for chronic low back pain to unimodal, biomedically focused care-as-usual in symptomatic, conservatively managed adult spinal deformity (ASD) patients. Methods A comparative cohort study of a biopsychosocial intervention cohort ( n =95) and a care-as-usual cohort ( n =95). Inclusion criteria of both cohorts: age ≥18, no surgical indication, Oswestry Disability Index (ODI)>20, coronal Cobb angle ≥20, idiopathic (AdIS) or degenerative (de novo) scoliosis (DN), baseline and one-year follow-up ODI data. Primary outcome: functional status (ODIv2.1a). Secondary outcomes: pain intensity (NPRS) and quality of life (SF36-PCS and SF36-MCS). Clinical relevance: minimal important clinical change (MCIC; improvement in ODI≥10 points), patient acceptable symptom state (PASS; ODI≤22). Results At one-year follow-up the patients in the biopsychosocial intervention cohort showed significantly greater improvement in functional status (ODI) compared to the care-as-usual cohort ( z =-3.97, p =